Cover Image. (29th October 2019) - Ericsson, Olle; Ahola, Tarja; Dahl, Fredrik; Karlsson, Filip; Persson, Fredrik; Karlberg, Olof; Roos, Fredrik; Alftrén, Ida; Andersson, Björn; Barkenäs, Emelie; Boghos, Ani; Brandner, Birgit; et al.
Abstract : The cover image is based on the Original Article Clinical validation of a novel automated cell‐free DNA screening assay for trisomies 21, 13, and 18 in maternal plasma by Olle Ericsson et al., https://doi.org//10.1002/pd.5528